Patterns of inter-state irregular migration in Africa: insights from Ethiopian migrants to the Republic of South Africa - Megersa, Hailu; Tafesse, Tesfaye (Frontiers in Human Dynamics, 2024)
Recent research suggests a significant rise in both international and intra-African migrations, with South Africa emerging as the primary destination for irregular migrants in the region.However, the phenomenon of irregular migration to South Africa has received limited attention despite the growing number of migrants hosted by the country. To address this gap, this study adopts a concurrent cross-sectional mixed-methods approach to explore the patterns of inter-state irregular migration in Africa, specifically focusing on Ethiopian migrants to the Republic of South Africa (RSA). The investigation draws on quantitative data collected from 316 migrant returnees, as well as qualitative in-depth interviews and focus-group discussions. The findings of this study reveal that there is a decline in the patterns of Ethiopian irregular migration to the RSA within the past decade due to tight legal restrictions. The COVID-19 pandemic has had a significant impact on the pattern of irregular migration, leading to a decline in the number of migrants from mid-2018 to 2020 due to stringent border closures. Irregular migration to the RSA tends to be temporary, with an increasing migrants returning to their home country once they have achieved economic success or as they encountered precarious conditions at the destination.Addressing the root causes that drive migration, improving border control mechanisms, and implementing inclusive integration strategies are key steps towards minimizing the risks and maximizing the benefits associated with this migration phenomenon.